2005
DOI: 10.1021/ja051223y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Imaging and Localization in the Neuronal Membrane

Abstract: Vitamin E (alpha-tocopherol) has been implicated in several cellular processes including signaling, transport, lipid membrane curvature, and several neurodegenerative disorders. Vitamin E imaging has been hindered by the inaccessibility of the molecule to traditional immunohistochemical methods. Using time-of-flight secondary ion mass spectrometry (ToF-SIMS), the distribution of major constituents in the cellular membrane of isolated neurons was investigated. There is a significant increase in the vitamin E si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(159 citation statements)
references
References 23 publications
3
154
0
2
Order By: Relevance
“…For example, Monroe et al showed that vitamin E (m/z 430) was localized at the junction of the cell soma and neurite in single isolated neurons of the California sea slug. 38 Lipid localization in cell membranes has also been observed in both glial and neuroblastoma cells. 37,39 C 60 + primary ion sources have generally not been used to image cells because they are typically focused to only ∼1 µm.…”
Section: Biological Imaging Of Tissues and Cellsmentioning
confidence: 99%
“…For example, Monroe et al showed that vitamin E (m/z 430) was localized at the junction of the cell soma and neurite in single isolated neurons of the California sea slug. 38 Lipid localization in cell membranes has also been observed in both glial and neuroblastoma cells. 37,39 C 60 + primary ion sources have generally not been used to image cells because they are typically focused to only ∼1 µm.…”
Section: Biological Imaging Of Tissues and Cellsmentioning
confidence: 99%
“…This technique has already been used to image tocopherol location in cells [102] and tissues [103][104][105]. It would be fascinating if someone should now apply the tools of lipidomics to collecting data not only on the location of tocopherol, but also the phospholipid profile at the same location.…”
Section: Is All Of This Relevant For Understanding the Biological Actmentioning
confidence: 99%
“…1 Numerous analytical techniques, including electrochemical detection, 2-6 separation-based methods, 7-9 fluorescence microscopy, 10-13 and mass spectrometry [14][15][16][17][18][19][20][21][22][23][24] have been used to surmount the inherent difficulties of measurements down to the μm-, pL-, and zmole-scale to study the intricate chemistry that exists within single cells.…”
Section: Introductionmentioning
confidence: 99%